Sacred Mobilities in Byzantium and Beyond
1 online resource (384 pages)
Keywords: Questions about space and the sacred are now central to Byzantine studies. Recent scholarship has addressed issues of embodiment and performance, power and identity, environmental perceptions and territorial imaginations. At the same time, the mobility turn in the humanities prompts new approaches to and understandings of processes of circulation of people, objects and ideas. Drawing together illuminating contributions from scholars in history, art history, literature, geography, architecture and theology, Sacred Mobilities in Byzantium and Beyond sets the stage for further cross-disciplinary dialogue concerning Orthodox Christian spiritual culture and society in the Byzantine Empire and in the centuries after its fall. Contributors are Veronica della Dora, Ekaterine Gedevanishvili, Molly Greene, Mark Guscin, Christos Antonios Kakalis, Chrysovalantis Kyriacou, Maria Litina, Andrew Louth, Mihail Mitrea, Bissera Pentcheva, Rehav Rubin, and David Williams.